A Well-Made Bed - Frucht, Abby; Alberts, Laurie (Book collections on Project MUSE., 2016)
"When do-gooder Noor and frumpy home-schooled Jaycee find in Jaycee's luggage a cheese stuffed with drugs that she has unwittingly smuggled home from Peru, greed overcomes good instincts, and soon the unlikely pair are breaking bad in Vermont. Noor, a therapeutic riding instructor, and Jaycee, daughter of a plagiarizing children's book author who has insisted on raising her as though it's still 1860, discover that they have more than selling drugs in common, including Gerry Wilcox, a sexy slacker admirer of Noor's, recruited to find them a connection. Ugly secrets, including the truth about the death of a childhood friend, some outrageous revelations about Jaycee's increasingly enfeebled parents, and Noor's burgeoning doubts about her marriage and motherhood, come to light as Jaycee and Noor make tentative strides toward a less prickly, though still lopsided friendship. A road trip to Miami in pursuit of more drugs brings them face to face with their capacity for betrayal, and a caper becomes a calamity. Darkly comic and beautifully rendered, A WELL-MADE BED goes beyond the tropes of the buddy tale to explore just how easily each of us might step over the line from being a clean-nosed good citizen to being a felon"--